2002
DOI: 10.1007/s00425-002-0800-y
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of viral RNA biosynthesis with glucose-6-phosphate dehydrogenase activity and host resistance

Abstract: Changes in glucose-6-phosphate dehydrogenase (G6P DH; EC 1.1.1.49) activity caused by infection of tobacco ( Nicotiana tabacum L.) leaves with potato virus Y (PVY), cucumber mosaic virus, potato virus X, tobacco rattle virus and turnip mosaic virus, the subcellular localisation of G6P DH isozymes in mesophyll protoplasts derived from healthy and PVY-infected tobacco leaves, as well as G6P DH control and the relationship of its isozymes with the degree of tobacco resistance to PVY multiplication, were studied. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…G6PDH has been shown to respond to various oxidative stresses and viral infection at the level of mRNA abundance or enzyme activity (Batz et al 1998, Nemoto and Sasakuma 2000, Šindelář and Šindelářová 2002. To clarify whether the change of the G6PDH activity under heat stress results from elevated protein content or specific activity, Western-blot analysis was carried out.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…G6PDH has been shown to respond to various oxidative stresses and viral infection at the level of mRNA abundance or enzyme activity (Batz et al 1998, Nemoto and Sasakuma 2000, Šindelář and Šindelářová 2002. To clarify whether the change of the G6PDH activity under heat stress results from elevated protein content or specific activity, Western-blot analysis was carried out.…”
Section: Resultsmentioning
confidence: 99%
“…It has been indicated that G6PDH plays a protective role against oxidative stress (Kletzien et al 1994, Pandolfi et al 1995. G6PDH is also involved in nitrogen assimilation (Oji et al 1985, Bowsher et al 1989, Esposito et al 2003, response to pathogenesis (Šindelář andŠindelářová 2002, Scharte et al 2009), metal toxicity (Esposito et al 1998), salt stress (Nemoto and Sasakuma, 2000, Liu et al 2007, Wang et al 2008 and combination of drought and heat stress (Rizhsky et al 2004). It was found that under salt stress G6PDH is involved in maintenance of intracellular reduced glutathione (GSH) in reed callus (Wang et al 2008) or NADPH content in olive plants (Valderrama et al 2006).…”
Section: Introductionmentioning
confidence: 96%
“…In plants, G6PD activity is present in the plastids and cytosol (Debnam and Emes, 1999). G6PD activity has been positively correlated with environmental stresses such as salt stress (Valderrama et al, 2006;Wang et al, 2008), aluminum toxicity (Slaski et al, 2006), drought (Scharte et al, 2009), and infection by viral and fungal pathogens (Sindelár and Sindelárová, 2002;Scharte et al, 2009); by contrast, a decrease in chloroplastic G6PD activity has been shown to be beneficial for withstanding oxidative stress (Debnam et al, 2004). Thus, the role of G6PD in the stress response is currently unclear.…”
Section: Introductionmentioning
confidence: 99%